2006
DOI: 10.1590/s0004-27492006000500024
|View full text |Cite
|
Sign up to set email alerts
|

Different presentations of intraretinal fluid collections in optic disc pits: OCT study of 3 cases

Abstract: The congenital optic disc pit is a rare anomaly that can lead to major visual impairment associated with subretinal fluid accumulation. The authors describe the optical coherence tomography study of three cases of untreated congenital optic disc pits with different levels of visual impairment and its different presentations of intraretinal fluid collections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…This OCT finding was the most common configuration as observed in other reports published previously. [12][13][14][15][16][17][18][19] We found a hole in the outer retinal layers in only three eyes. We also detected only intraretinal schisis in one eye and only serous macular detachment in one eye by OCT evaluation.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This OCT finding was the most common configuration as observed in other reports published previously. [12][13][14][15][16][17][18][19] We found a hole in the outer retinal layers in only three eyes. We also detected only intraretinal schisis in one eye and only serous macular detachment in one eye by OCT evaluation.…”
Section: Discussionmentioning
confidence: 63%
“…ODP maculopathy has been suggested to initiate with inner retinal splitting such as schisis, then return to serous macular detachment after development of a hole in the external retinal layers through which the intraretinal fluid passes to the subretinal space. [12][13][14][15][16][17][18][19] It has been reported that detachment of external retinal layers occurred secondarily in a group of patients in whom 10 out of 11 eyes had double layer detachment and 7 had a hole in external retinal layers. 22 However, it was shown in a high resolution OCT study that a hole in the external retinal layers was not a common finding and that the fluid could pass through the optic pit directly into all layers of the sensorial retina, especially to beneath the internal limiting membrane, ganglion cell layer, and inner and outer nuclear layers in addition to the subretinal space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, OCT reveals the dual morphology of the detachment with a schisis cavity (in the majority of patients) and with a coexisting outer layer detachment from the retinal pigment epithelium (Figs. 5 and 6) [13,[44][45][46]. OCT may also reveal retinal edema in the inner layers, with cystic degeneration overlying a more central detachment [14], although the most prominent edema is located in the outer layers.…”
Section: Diagnosis Of Odp-mmentioning
confidence: 99%
“…Serous macular retinal detachment is associated with 25% to 75% of optic nerve head pits (2)(3)(4) . Using the cross-sectional retinal imaging provided by optical coherence tomography (OCT), several authors have confirmed the concept of a bilaminar structure with schisis-like retinal changes overlying a more central neurosensory retinal detachment (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 94%